(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Molecular detection of Plasmodium falciparum based on PCR amplification is generally very specific and sensitive test for determining the species of Plasmodium present in the blood of an individual than the microscopy-based diagnosis from blood smears. Thirty-two (32) microscopic malaria positive blood samples were collected from some patients between November 2013 to March 2014 from three major hospitals.Plasmodium DNA was extracted from the 32 blood samples collected from the malaria-positive patients confirmed by microscopy and the DNA amplification was done by using Polymerase Chain Reaction (PCR). The amplified COX3 gene of each malaria isolates were further characterized using Agarose gel electrophoresis while sequence identification was performed by using GenBank’s BLAST algorithm. After the completion of the agarose gel electrophoresis the bands indicating amplified Cox3 gene by PCR was observed in four (4) plasmodium positive blood samples out of the 32 samples analyzed. Amplified band for COX3 gene was located at 300bp position on the DNA ladder on the agarose gel plate for sample 1, 9 and 24 all from Kagarko general hospital while sample 28 was from GwannaAwan general hospital. The BLAST results showed that the P. falciparum DNA sequences aligned at 98-99% similarity with those deposited in the GenBank confirming the parasite isolated from the patients were P. falciparum. The use of PCR diagnosis to compliment microscopy examination of stained blood smears in our medical centres is strongly recommended so that an accurate detection of malaria parasites in blood will help to institute proper drug therapy